Channel Characterization and Robust Tracking for Diversity Reception over Time-Variant Off-Body Wireless Communication Channels. (20th July 2010) - Van Torre Van Torre, Patrick Patrick; Vallozzi Vallozzi, Luigi Luigi; Rogier Rogier, Hendrik Hendrik; Moeneclaey Moeneclaey, Marc Marc; Verhaevert Verhaevert, Jo Jo
Abstract : In the 2.45 GHz band, indoor wireless off-body data communication by a moving person can be problematic due to time-variant signal fading and the consequent variation in channel parameters. Off-body communication specifically suffers from the combined effects of fading, shadowing, and path loss due to time-variant multipath propagation in combination with shadowing by the human body. Measurements are performed to analyze the autocorrelation, coherence time, and power spectral density for a person equipped with a wearable receive system moving at different speeds for different configurations and antenna positions. Diversity reception with multiple textile antennas integrated in the clothing provides a means of improving the reliability of the link. For the dynamic channel estimation, a scheme using hard decision feedback after MRC with adaptive low-pass filtering is demonstrated to be successful in providing robust data detection for long data bursts, in the presence of dramatic channel variation.